GOOD GOVERNANCE DALAM PERSPEKTIF PENGUATAN PERAN GENDER DALAM BINGKAI AGAMA - Syibly, M. Roem (Millah: Journal of Religious Studies, 2007)
On Good Governance perspective, Indonesia has given positive contribution toward gender issues. Legally, Indonesia has fulfilled all conditions as state with good governance, but unfortunately, at the field showed that such ordinances issued were ineffective. PSI-UII’s research report has found any correlation between violence toward women and religious understanding. In the field finding will give inputs to all people who concern with the issue. Several Muslim scholars already give us some solution with interpretation toward al-Quran and Hadits, which support gender justice and equality. Government and all organization involved, have to support law and its instrument can be applied well.